Effect of antidepressant treatment on peripheral inflammation markers – A meta-analysis - Więdłocha, Magdalena; Marcinowicz, Piotr; Krupa, Renata; Janoska-Jaździk, Marlena; Janus, Marta; Dębowska, Weronika; Mosiołek, Anna; Waszkiewicz, Napoleon; Szulc, Agata (Progress in neuro-psychopharmacology & biological psychiatry, 2018)
Major Depressive Disorder (MDD) in accordance to the inflammatory concept is associated with complex immunological disturbances in the central nervous system (CNS). This is reflected by elevated plasma levels of inflammatory cytokines in depressed subjects. Although numerous studies report significant influence of antidepressants on pro-inflammatory/anti-inflammatory cytokines balance, the available data is often inconsistent regarding specific cytokines and drugs used. We aimed to perform a comprehensive meta-analysis of the effect of antidepressant treatment on a wide array of cytokines. We performed a systematic search of 6 databases, which yielded 32 studies measuring the levels of selected cytokines before and at a second time-point during antidepressant treatment. For meta-analysis of selected studies with a continuous measure we analysed variables containing the number of cases, mean and standard deviation of the level of IL-1ß, IL-2, IL-5, IL-6, IL-8, IL-10, CRP, TNF-α, IFN-γ levels observed in the different studies, in the intervention groups before and after antidepressant treatment. Statistical analysis revealed significant decreases of IL-4, IL-6, and IL-10 in MDD subjects after antidepressant treatment. In case of IL-1ß the decrease was significant exclusively for SSRI drugs. We did not find any significant effect of antidepressant medication on IL-2, TNF-α IFN-γ and CRP. Antidepressant treatment affects the levels of cytokines in depression. The immunological imbalance in MDD is complex and seems to be mediated by other factors yet to be elucidated. The credibility of our results is limited by high heterogeneity among studies and very few studies with a placebo-controlled design. Research with MDD subtypes, response to treatment status and cytokine associations with the kynurenine pathway taken into account pose a promising target for future studies.